Incredible jobs you've (probably) never heard of - Labarre, Natalie (Nosy Crow, an imprint of Candlewick Press, 2020)
Do you know what you want to do when you grow up? Why not work as a babysitter ... for sloths? Or become a farmer ... of corpses? You might even grow up to be someone who gets paid to actually sleep on the job! From taste testers to dinosaur dusters, there are all kinds of incredible jobs that you've probably never heard of ... and one of them might be just right for you!--description from publisher.